Multivariate public key cryptosystems - Ding, Jintai; Gower, Jason E.; Schmidt, Dieter S. (Advances in Information Security, 2006)
Multivariate public key cryptosystems (MPKC) is a fast-developing area in cryptography. This book systematically presents the subject matter for a broad audience and is the first book to focus on this exciting new topic.